"Humbling experiences": A photovoice project with sexual and gender‐expansive youth experiencing homelessness. Issue 6 (25th March 2018) - Forge, Nicholas; Lewinson, Terri; Garner, Brittany M.; Braxton, Charlayna; Greenwald, Lindsay; Maley, Olivia
Abstract: While experiencing homelessness, queer youth are subject to stereotyping, discrimination, and violence that affect their ability to achieve independent living and actualize goals. Lesbian, gay, bisexual, transgender, and queer (LGBTQ)‐identified youth of color are at greater risk for homelessness when compared to heterosexual counterparts. This study explores lived experiences of queer‐identified youth of color who are currently experiencing homelessness. Using photovoice methodology, a group of 4 participants drawn from an Atlanta‐based service provider for LGBTQ youth were engaged in a series of focus groups to discuss meaningful photographic images and give voice to shared homelessness experiences. From their individual and collective narratives, three key themes were identified: becoming aware, managing inner struggles, and recognizing personal strengths. The participating youth marked the conclusion of the project by presenting to youth service practitioners a poster board display of photos that visually represented areas of concern and opportunities for ongoing advocacy to benefit this underserved and often misunderstood population. This study also reports on this poster board display and the outcomes identified by the participating young people for better supporting homeless LGBTQ young people.